Dreams of Germany : musical imaginaries from the concert hall to the dance floor - Gregor, Neil, 1969-; Irvine, Thomas (New York : Berghahn Books, 2019)
"For many centuries, Germany has enjoyed a reputation as the 'land of music'. But just how was this reputation established and transformed over time, and to what extent was it produced within or outside of Germany? Through case studies that range from Bruckner to the Beatles and from symphonies to dance-club music, this volume looks at how German musicians and their audiences responded to the most significant developments of the twentieth century, including mass media, technological advances, fascism, and war on an unprecedented scale"--
"The German in the concert hall" : concert-going and belonging in the early twentieth century / Hansjakob Ziemer -- "Music made in Hamburg" : how one city's music scene helped make rock and roll the lingua franca of youth / Julia Sneeringer -- "With every inconceivable finesse, excess and good music" : sex, affect, and techno at Snax Club in Berlin / Luis-Manuel Garcia -- Bruckner, Munich, and the Longue Duree of musical listening between the imperial and post- war eras / Neil Gregor -- Female musicians and "Jewish" music in the Jewish Kulturbund in Bavaria, 1934-1938 / Dana Smith -- Pride of place : the 1963 rebuilding of the Munich Nationaltheater / Emily Richmond Pollock -- Was ist Japanisch? Wagnerism and dreams of nationhood in modern Japan / Brooke McCorkle -- Hubert Parry, Germany, and the "North" Thomas Irvine -- Between musicology and mythology at the Stunde Null : Austria's 950th "birthday" and the 50th anniversary of Bruckner's death / Lap-Kwan Kam -- Hearing the Nazi Past in the German Democratic Republic : antifascist fantasies, acoustic realities, and haunted memories in Georg Katzer's Aide-memoire (1983) / Martha Sprigge -- Sprockets + Autobahn : Kraftwerk parodies, German electronic music, and retro dreams in Amerika / Sean Nye.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 20, 2018).
eBooks on EBSCOhost
Keywords: Music -- Social aspects -- Germany -- History -- 20th century; Music -- Germany -- 20th century -- History and criticism; National characteristics, German; Music -- German influences; Musique -- Aspect social -- Allemagne -- Histoire -- 20e siècle.; Allemands; MUSIC -- Genres & Styles -- Classical; MUSIC -- Reference; MUSIC -- History & Criticism; Music; Music -- German influences; Music -- Social aspects; National characteristics, German; Germany; 1900-1999; Criticism, interpretation, etc; History